¿Son útiles las TIC para combatir la ciberdelincuencia? La relación entre la denuncia de delitos informáticos y el equipamiento tecnológico de las comisarías - Fernández, William; Vargas, Carmen (Law, State and Telecommunications Review, 2018)
Purpose ”“ Computer crimes are serious and recent problems in Peru. The easy access to technology and the socioeconomic conditions of the country have made it a favorable place to commit cybercrimes. On the other hand, the agents involved, such as the police, are often at a disadvantage, as they do not have the necessary skills to combat those crimes. It is relevant to ask whether the ability of the police to use Information and Communication Technologies (ICT) works as a marker that serves to deter criminals from committing crimes. Methodology/approach/design ”“ A database was constructed from sources of information on police stations and crimes in Peru. With this, a probit model was estimated in which the dependent variable is the probability of the occurrence of computer crimes. The marginal effects of three indices constructed from variables indicating the use of ICT were calculated. Findings ”“ The results obtained show that two of our three indices explain that, the greater the use of ICT in Peruvian police stations, there is a lower probability of the occurrence of cybercrimes.